SOCIAL MEDIA IN THE DEVELOPMENT OF THE ATHLETE'S DUAL CAREER - Onose Ionuț; Onose Raluca-Mihaela; Iconomescu Teodora-Mihaela; Talaghir Laurentiu-5Gabriel; Ripert Fabio; Abalașei Beatrice-Aurelia (Sport şi Societate)
Throughout their performance careers, athletes are forced to fulfill multiple social roles at the 1same time and are forced to manage, with the help of their family, school or sports environment, their dual careers. Mass media can influence the public if theyuse modeling theory. A person from the public sees (or reads) through the media about another person (who is a model) and wants to identify with him, because he considers the model as successful, attractive and worthy of imitation. The purpose of the study is to determine if there is an influence of social media on the dual career of athletes. The subjects of the research are 12th-grade students of High Schools With A Sports Program, aged between 17-19 years, who answered the questions of a questionnaire. The Chi-Square Test of Independence was used in the research, which determined whether, from a statistical point of view, the answers obtained are associated. The obtained results can be starting points in the implementation of government policies regarding the implementation of the dual career in Romania.